PENGARUH HARGA MINYAK DUNIA, INFLASI, DAN EKSPOR NETO TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Anggun Mai Safitri; Khairil Anwar; Tarmizi Abbas (LPPM UNIMAL, 2022)
This study examined the effect of world oil prices, inflation, and net exports on economic growth in Indonesia. This study used time-series data from 1981-to 2020 obtained from the Central Bureau of Statistics of Indonesia and Bank Indonesia. The data were then analyzed using Autoreggresive Distributed Lagregression analysis with the help of Eviews. The results indicated that oil prices and net exports positively and significantly influenced economic growth in Indonesia. It means that if oil prices and net exports increase, then economic growth in Indonesia will also increase. Meanwhile, inflation negatively and insignificantly influenced economic growth in Indonesia. It indicates that if inflation increases, the economic growth in Indonesia will decrease.